Analisis User Experience Aplikasi SwapEase Menggunakan Metode User Experience Questionnaire (UEQ) - Nisrina Qurratu Aini; Jumrianto; Dhega Febiharsa (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
The optimization of the SwapEase application needs improvement to ensure users have a satisfying experience. SwapEase supports digital clothing exchanges to reduce the impact of fast fashion. This research approach uses the User Experience Questionnaire (UEQ) method. Six main dimensions are measured: attractiveness, clarity, efficiency, dependability, stimulation, and novelty. A survey was conducted among active users, and the data were analyzed using the UEQ Data Analysis Tool version 12 to produce average scores and standard deviations for each dimension. The analysis results show that the Attractiveness dimension received an average score of 1.17, Clarity 1.05, Efficiency 1.13, Dependability 1.01, Stimulation 1.15, and Novelty 0.87. SwapEase excels in efficiency, stimulation, and novelty, with scores above the benchmark average, reflecting positive perceptions of the application’s effectiveness and innovation. However, the dimensions of attractiveness, clarity, and dependability remain below average, indicating a need for improvements in visual appeal, usability, and reliability. By enhancing these less optimal aspects, SwapEase can better meet user needs and compete more effectively in the digital application market.